2014
DOI: 10.1038/nrcardio.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Robotic technology in cardiovascular medicine

Abstract: Robotic technology has been used in cardiovascular medicine since the late 1990s. Interventional cardiology, electrophysiology, endovascular surgery, minimally invasive cardiac surgery, and laparoscopic vascular surgery are all fields of application. Robotic devices enable endoscopic reconstructive surgery in narrow spaces and fast, very precise placement of catheters and devices in catheter-based interventions. In all robotic systems, the operator manipulates the robotic arms from a control station or console… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 52 publications
1
46
0
1
Order By: Relevance
“…The basic feasibility and safety of approaches involving robotics technology in cardiovascular medicine have been demonstrated. 11 Excision of cardiac tumors has been particularly amenable to minimally invasive approaches. The da Vinci Surgical System provides assistance to surgeons via telemanipulation through a master-controller activation principle with a 3-dimensional intracardiac camera.…”
Section: Discussionmentioning
confidence: 99%
“…The basic feasibility and safety of approaches involving robotics technology in cardiovascular medicine have been demonstrated. 11 Excision of cardiac tumors has been particularly amenable to minimally invasive approaches. The da Vinci Surgical System provides assistance to surgeons via telemanipulation through a master-controller activation principle with a 3-dimensional intracardiac camera.…”
Section: Discussionmentioning
confidence: 99%
“…So far, observational data have suggested that these procedures are safe and that patients recover significantly faster than with CABG in the early postoperative period 125, 126, 127. Furthermore, there may also be benefits related to periprocedural morbidity compared with CABG 125…”
Section: Minimally Invasive Cabg Total Endoscopic Coronary Artery Bymentioning
confidence: 99%
“…However, as a natural step forward, robotics designers have found new and exciting frontiers to expand the existing research toward human-centered fields. Robots are now physically interacting with humans, especially in the medical domain (Colombo et al, 2001; Hochberg et al, 2012; Bonatti et al, 2014). This whole new field of robotics is evolving toward closing the gap between mechatronic systems and humans.…”
Section: Introductionmentioning
confidence: 99%